Eco-bioremediation potential of mealworm gut microbiome for polystyrene degradation in nutrient-based media - Afandi Afandi; Popi Septiani; Azzania Fibriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Polystyrene is a petroleum-based polymer widely used in single-use packaging and thermal insulation. Its high molecular weight and structural stability make it highly resistant to degradation, leading to persistent environmental accumulation. Recent studies have highlighted the potential of insect gut microbiota, particularly from mealworms, to biodegrade plastic waste. In this study, gut extracts were inoculated into Nutrient Broth (NB) and Potato Dextrose Broth (PDB), each supplemented with polystyrene as emulsion, powder, or film. NB showed the highest reduction in polystyrene weight (0.93%) by day 28, compared to PDB (0.73%). Total plate count and yeast-mold count analyses revealed microbial proliferation in both media, with NB exhibiting a higher final bacterial count (7.562 log cfu/mL) than PDB (6.510 log cfu/mL), while fungal counts were comparable. Scanning Electron Microscopy confirmed structural damage to polystyrene films, including surface roughening and micro-pitting, especially in NB. These findings indicate that media composition significantly influences microbial growth and degradation efficiency. NB appears to favor bacterial communities with enhanced plastic-degrading capabilities, demonstrating superior biodegradation potential in liquid culture.